PENGARUH KOMPENSASI BONUS, DIVERSIFIKASI PERUSAHAAN, KEPEMILIKAN MANAJERIAL, UKURAN KAP, UKURAN PERUSAHAAN DAN GOOD CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017-2019 - Aodina Latifah Khulsum; iing lukman; Indah lia puspita (Universitas Malahayati, 2022)
This researcher aims to determine the effect of bonus compensation, company diversification, managerial ownership, size of auditor firm, firm size and good corporate governance have on earnings management. The research was conducted on 76 manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. Hypothesis testing in this study was carried out using multiple linear regression analysis methods in the SPSS version 21 application program. The results showed that the Bonus Compensation variable (X1) had a regression coefficient with a negative direction of 0.021. with a significance value of 0.020. The company diversification variable (X2) has a regression coefficient with a negative direction of 0.013 with a significance value of 0.306. Managerial Ownership Variable (X3) has a regression coefficient with a negative direction of 0.038 with a significance value of 0.033. The size of auditor firm variable (X4) has a regression coefficient with a negative direction of 0.004 with a significance value of 0.591. The firm size variable (X5) has a regression coefficient with a positive direction of 0.008 with a significance value of 0.034. The variable of the Board of Commissioners (X6) has a regression coefficient with a positive direction of 0.002 with a significance value of 0.499. The Audit Committee variable (X7) has a regression coefficient with a negative direction of 0.005 with a significance value of 0.607. The Audit Quality Variable (X8) has a regression coefficient in a negative direction of 0.014 with a significance value of 0.143. And based on the simultaneous test of Bonus Compensation, Company Diversification, Managerial Ownership, KAP size, size of auditor firm, Board of Commissioners, Audit Committee and Audit Quality together have an effect on Earning Management. The result of the test of the coefficient of determination R2 is 8.64.Keywords: Bonus Compensation, Company Diversification, Managerial Ownership, size of auditor firm, firm Size, Board of Commissioners, Audit Committee, Audit Quality and Earnings Management